INSTALASI JARINGAN KOMPUTER SEBAGAI PENUNJANG LAYANAN ADMINISTRASI MASYARAKAT DESA KARANGDUREN KAB. MALANG - Yuri Ariyanto; Atiqah Nurul Asri; Yoppy Yunhasnawa; Faiz Ushbah Mubarok; Mungki Astiningrum (Publisher UPT P2M Politeknik Negeri Malang, 2022)
At the village level, administrative services are the main service and are directly related to the needs of the community. Administrative services can be in the form of issuing certificates, cover letters, letters of recommendation, legalization, and other letters. For administrative services in correspondence, the problems faced by the Karangduren village office regarding the installation of computer networks. Currently, computers that store data and applications for mailing repositories are not yet connected to other computers, resulting in queuing and slow document processing. With these problems, PPM (Pengabdian Pada Masyarakat) activities will be carried out in the form of